Psychological Factors of Personal Activity Formation in Modern Adolescents. Approach to the Problem - Levitskaya, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article contains a theoretical analysis of the psychological factors of personal activity formation in modern adolescents. Discusses the question of psychological conditions for the development of personal potential and personal activity in the educational environment and the psychological determinants of personality professionalization. Fundamental factors of personal activity formation were identified. Defined the significance of psycho-pedagogical support of modern adolescents in stage career choice.